Characteristics and analysis of risk factors for mortality in infective endocarditis - Leblebicioglu, H; Yilmaz, H; Tasova, Y; Alp, E; Saba, R; Caylan, R; Esen, S (Springer, 2006)
Objective: The aim of our study was to establish the etiology of and risk factors for infective endocarditis (IE) and determine the prognostic factors for adverse outcome during hospital admission in a Turkish population. Material and Methods: Between January 2002 and January 2004, the clinical and laboratory features of 112 consecutive adult patients (> 18 years) with diagnosis of IE who were referred to the infectious diseases clinics/departments of 17 teaching hospitals in Turkey were evaluated. Cases of IE were defined according to the modified Duke Criteria. Mortality was defined as death occurring within 30 days or during hospital stay period. Univariate and multivariate analyses were performed to predict the factors related to fatal outcome. Results: A total of 112 consecutive patients presented with 101 definite and 11 probable IE episodes were defined according to the modified Duke Criteria. The mean age was 45.2 +/- 19.9. Fifty percent of the patients were male. Ninety (60.4%) of the 112 patients had risk factors for IE and 48 (42.9%) of them had >= 2 risk factors. On the other hand, 49.1% of patients had cardiac risk factors. Blood cultures were positive in 94 (83.9%) cases. Staphylococci were the most common agents (50.0%), followed by streptococci (28.7%) and enterococi (16.0%). Native cardiac valves were detected in 93 (83%) of the episodes of suspected IE. Valvular involvement was present in 103 (92%) patients; the mitral valve, alone or in combination with other valves, was affected in 70 (62.5%) of the patients. Echocardiography detected vegetations in 105 patients (93.8%). The mortality rate was 28.6%. Three factors were independently associated with mortality: haemodialysis OR: 14.5 (95% CI: 1.5-138.2), mobile vegetation OR: 4.8 (95% CI: 1.5-15.4) and mental alteration OR: 4.1 (95% CI: 1.1-15.6). Conclusion: Mortality is still high in IE. Our data indicate that patients with altered mental status, mobile vegetation, or on haemodialysis had poorer prognosis.
Keywords: endocarditis; haemodialysis; mental alteration; mortality; prognosis; vegetation